2009
DOI: 10.1159/000230709
|View full text |Cite
|
Sign up to set email alerts
|

How Well Do the ADAS-cog and its Subscales Measure Cognitive Dysfunction in Alzheimer’s Disease?

Abstract: Background/Aims: The Alzheimer’s Disease Assessment Scale-cognitive (ADAS-cog) is regularly used to assess cognitive dysfunction in Alzheimer’s disease (AD) clinical trials. Yet, little is known about how the instrument and its subscales measure cognition across the spectrum of AD. The current investigation used item response theory (IRT) analyses to assess the measurement properties of the ADAS-cog across the range of cognitive dysfunction in AD. Methods: We used IRT-based analyses to establish the relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
53
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 33 publications
6
53
0
Order By: Relevance
“…these observations are in line with recent publications that bring into question the sensitivity of adascog in mild cognitive impairment and mild ad (17)(18)(19). this may be due to the poor psychometric properties of the adascog measure, such as inadequate assessment of cognitive domains such as attention, working memory and executive function (19,20) and the presence of floor effects (17). Furthermore, several recent studies have reported slower rates of placebo decline in ad patients than traditionally assumed by older models and clinical trials (12,(21)(22)(23); they have also shown that baseline adas-cog significantly affects the rate of ad progression (23,24).…”
Section: Effects Of a Medical Food On Cognition In Ad The Journal Of supporting
confidence: 93%
See 1 more Smart Citation
“…these observations are in line with recent publications that bring into question the sensitivity of adascog in mild cognitive impairment and mild ad (17)(18)(19). this may be due to the poor psychometric properties of the adascog measure, such as inadequate assessment of cognitive domains such as attention, working memory and executive function (19,20) and the presence of floor effects (17). Furthermore, several recent studies have reported slower rates of placebo decline in ad patients than traditionally assumed by older models and clinical trials (12,(21)(22)(23); they have also shown that baseline adas-cog significantly affects the rate of ad progression (23,24).…”
Section: Effects Of a Medical Food On Cognition In Ad The Journal Of supporting
confidence: 93%
“…Within the group of patients with higher adas-cog scores at baseline, souvenaid significantly improved adas-cog scores compared with the control group. these observations are in line with recent publications that bring into question the sensitivity of adascog in mild cognitive impairment and mild ad (17)(18)(19). this may be due to the poor psychometric properties of the adascog measure, such as inadequate assessment of cognitive domains such as attention, working memory and executive function (19,20) and the presence of floor effects (17).…”
Section: Effects Of a Medical Food On Cognition In Ad The Journal Of supporting
confidence: 88%
“…19,35 The ADAS-Cog is most sensitive to change in patients with moderate disease. 36,37 Since the NTB captures changes in delayed memory and executive function which are not well-covered by the ADAS-Cog, our findings support the choice of the NTB for studies in mild AD.…”
Section: Discussionsupporting
confidence: 59%
“…Considering the difference in underlying neural networks, it is likely that sensitivity to change on enhancement of neurotransmission is different for these aspects even though they are summarized as ‘cognition’. It has already been reported that the ADAS-cog and its subscales provide maximum information at moderate levels of cognitive dysfunction [3]. Raw score differences toward the lower and higher ends of the scale corresponded to large differences in cognitive dysfunction, whereas raw score differences toward the middle of the scale corresponded to smaller differences [3].…”
Section: Introductionmentioning
confidence: 99%
“…It has already been reported that the ADAS-cog and its subscales provide maximum information at moderate levels of cognitive dysfunction [3]. Raw score differences toward the lower and higher ends of the scale corresponded to large differences in cognitive dysfunction, whereas raw score differences toward the middle of the scale corresponded to smaller differences [3]. In fact, in more severe stages of disease the ADAS-cog loses its sensitivity of change so much that the severe impairment battery was developed to assess patients who are unable to complete tests such as the ADAS-cog [24].…”
Section: Introductionmentioning
confidence: 99%